Professional Competence of Prospective Elementary School Teachers in Designing Lesson Plans Integrating Project-Based Learning Models and TPACK - Fazilla, Sarah; Bukit, Nurdin; Sriadhi, Sriadhi (Universitas Pendidikan Indonesia, 2023)
During the industrial revolution, the quality of education improved, and this was reflected in competent and professional teachers. Teacher professional competence can be achieved by combining personal, scientific, technological, social, and spiritual skills.. This study aims at assessing prospective teachers' professional abilities in developing lesson plans that are integrated with the Project Based Learning and TPACK models in Microteaching course. This study employs a qualitative approach with a case study research design by involving 10 prospective elementary school teachers enrolled in sixth semester. Data collection was carried out through interviews, observation, and documentation, while data analysis was carried out qualitatively, comprising data reduction, verification, and conclusions. The findings obtained revealed that the professional competence of prospective elementary school teachers was adequate but could be improved. According to the interviews, they were able to develop a scientific mindset in preparing lesson plans with subject mastery based on basic competencies and learning objectives. In fact, four participants were able to develop lesson plans using project-based learning models. In the analysis process, it was also found that these prospective elementary school teachers were able to integrate TPACK, meaning they knew how to link material with the use of technology and were able to teach it in simulation activities carried out in class. However, some of them still struggled to make project-based learning plans, especially in designing projects relevant to teaching materials. Overall, it can be concluded that the professional competence of prospective teacher students was adequate but could be improved, particularly in their capacity to design projects relevant to the material and learning objectives in elementary schools.